CHALLENGES FACED BY ECONOMICS STUDENTS IN ACQUIRING LANGUAGE PROFICIENCY FOR EFFECTIVE COMMUNICATION (Modern education and development, 2024)
Economics students face unique challenges in acquiring language proficiency, which is critical for effective communication in academic and professional settings. This study explores these challenges through linguistic, contextual, and pedagogical lenses. A mixed-methods approach was used to identify key difficulties, including limited exposure to specialized vocabulary, inadequate integration of language instruction into economics curricula, and varying levels of English proficiency. Findings suggest that targeted interventions, such as interdisciplinary collaboration and tailored language programs, can significantly enhance communication skills. These strategies are essential for enabling students to articulate complex economic concepts and engage effectively in global discussions.